EFFICIENCY OF MARKETING CHANNELS FOR MELON (Cucumis melo L.) IN THE GREEN HOUSE OF BALITAR ISLAMIC UNIVERSITY, BLITAR CITY - Luhur Aditya Prayudhi; Rona Asmara (Universitas Islam Balitar, 2023)
In the era of free market trade, competition is getting tougher. It is necessary to find a special market to boost the selling price of melons. High quality fruit offered will deserve a high selling price. The purpose of marketing margin analysis is to see the marketing efficiency indicated by the amount of profit received by each marketing actor. Based on the calculation of marketing margins and farmershare of the two marketing channels, channel I has the same amount of margin for grades A, B, and C have the same marketing margin of Rp 6000/kg. The farmer share value of channel I pattern for grade A is 70%, grade B is 62.5%, and grade C is 57.1%. Channel pattern II has a total margin for grade A of Rp 26,000/kg, grade B of Rp 20,000, and grade C of Rp 17,000/kg. The farmer share value of channel pattern II for grade A is 35%, grade B is 33.3%, and grade C is 32%. It can be concluded that the most efficient channel pattern in melon fruit sales at the Green House of Balitar Islamic University in Blitar City is channel pattern I, because it has the shortest marketing chain, namely producers directly to consumers.